Determinants Of Motor Vehicle Taxpayer Compliance In The Serang City - Intan Puspanita; Asih Machfuzhoh (Jurnal Akademi Akuntansi, 2022)
This study aims to examine the determinants of motor vehicle taxpayer compliance. The method used in this research is explanatory research. The population of this study are taxpayer at Samsat Office in the city of Serang. Accidental sampling method was used for the sample of this study. This research was carried out in stages, namely collecting data through questionnaires that were distributed to motor vehicle taxpayers and continued with data analysis. This research data is primary data and analyzed using validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test and multiple linear regression analysis test. The result of this study indicate that tax awarness, tax knowledge, income level, quality of tax services and tax sanctions have a significant effect on the compliance of motor vehicle taxpayer that registered in Samsat Office at the Serang City. This research is expected to contribute to the Samsat of Serang City to improve taxpayer compliance in fulfilling their tax obligation.